METHODOLOGY FOR ORGANIZING AND ORGANIZING CULTURAL AND ARTISTIC EVENTS IN EDUCATIONAL INSTITUTIONS - Mirzaev Bahrom Fayzullo o‘g‘li; Ilmiy rahbar: Raximov Sh. N. (Scholars Digest Publishing, 2023)
In many ways, the effectiveness of cultural and educational activities held in the education system in moral and ethical education is linked to the methodology of conducting them. Since ancient times, joy and zukko disputes have played a role as a means of educating young people.
Keywords: Event, music, students, enlightenment, upbringing, method.